Different Type of Application Edible Coatings Technique on Beef of Physcochemical an Sensory Quality - Mulia Winirsya Apriliyani; Premy Puspitawati Rahayu; Imam Thohari (Postgraduate, University of Mataram, 2022)
This study aimed to determine the best technique of application of edible coatings (spraying, spreading, or dipping) on beef carried out sensory quality, then performed in coated to physicochemical analyses (pH, moisture content, WHC, cooking loss, and color). This study aimed to determine the best technique of application of edible coatings (spraying, spreading, or dipping) on beef carried out sensory quality, then performed in coated to physicochemical analyses (pH, moisture content, WHC, cooking loss, and color). The beef was coated with different coating techniques spraying, brushing, and dipping then stored at 27Â°C for 8 hours. At the end of the storage period, the treatments exhibited the best sensory analyses (texture surface and under, odor, physical deviation, and discoloration). The best sensory analysis is the spraying of coatings technique is spraying. The results that the application of the edible coatings technique on beef maintaining the best physicochemical quality are pH 5,59; the moisture content of 68,26%; WHC of 43,71%; cooking loss of 34,28%; and color indicated by L*, a*, and b*.